Historical roots of entrepreneurial culture and innovation activity: An analysis for German regions - Michael Fritsch; Martin Obschonka; Michael Wyrwich (Friedrich Schiller University Jena, 2018)
There is a research gap with respect to understanding the role of entrepreneurial culture and tradition for actual start-up behaviour. We combine historical self-employment data (entrepreneurial tradition) with a psychological measure for entrepreneurial attitudes (entrepreneurial culture). The results reveal a positive relationship between the historical level of selfemployment in a region and the presence of people with an entrepreneurial personality structure today. Our measure for a regional culture of entrepreneurship is positively related not only to the level of new business formation but also the amount of innovation activity.
Keywords: L26; N94; O11; O30; R11; 330; entrepreneurship; self-employment; new business formation; personality traits; culture; innovation